(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article analyzes the characteristics of action verbs in French and Uzbek languages. The grammatical, semantic and pragmatic aspects of action verbs are studied in the article. In Uzbek, action verbs are formed using adverbs to express tense, person and number, and in French they are expressed in different tenses using them with auxiliary verbs. Changing action verbs depending on the context increases their role in communication. This study serves to create new concepts in the field of linguistics by showing the similarities and differences between action verbs in French and Uzbek languages.